A six-year retrospective study of maxillofacial fractures from radiographic findings in Brazil (Revista da Faculdade de Odontologia - UPF, 2013)
Objective: this study aimed to present the causes and prevalence of maxillofacial fractures that occurred in the region of Araraquara-SP – Brazil, during a 6-year period. Methods: information regarding age, gender, etiology, and maxillofacial fracture site, as well as type of radiographic examination were evaluated. Data were gathered from the radiographic examination and radiographic report of the Division of Dentomaxillofacial Radiology, and from charts of the Division of Oral and Maxillofacial Surgery of patients attending for maxillofacial fractures from 2004 to 2009. A descriptive statistical analysis was developed using Epi-Info 3.5.1. Results: from a total of 11,728 patients assisted, 407 patients presented maxillofacial fractures. The prevalent age ranged from 21 to 30 years old. From the total patients, 322 were men and 85 were women (ratio of men to women was 3.8:1). Panoramic radiography (n = 306) was most frequently used to observe maxillofacial fractures. Mandibular fractures were frequent in the body of the mandible (n = 127), followed by symphysis (n = 102), and the prevalent cause was traffic accidents (n = 161). Conclusion: more than half of affected individuals were younger than 40 years of age. The body of the mandible was the most common fracture location vi sualized by panoramic radiography for traffic accidentsand fights.